IMPLEMENTASI PENDIDIKAN AGAMA ISLAM BERBASIS KARAKTER SEBAGAI REPRESENTASI PARADIGMA BARU DALAM KONTEKS KONTEMPORER DI MA MAZRO’ATUL ULUM CITIIS - Asep Suherli; Mulyawan Safwandy Nugraha (CV. Adiba Aisha Amira, 2026)
Social, cultural, and technological transformations require Islamic Religious Education (IRE) to move beyond a classical, text-centered paradigm toward a contextual and character-oriented approach. This study analyzes the implementation of character-based Islamic Religious Education as a representation of the new paradigm of IRE in a contemporary educational setting. Using a qualitative field research design, the study was conducted at MA Mazro’atul Ulum Citiis with students and Islamic Religious Education teachers as research participants. Data were collected through classroom observations, in-depth interviews, and document analysis, and analyzed using an interactive qualitative analysis model. The findings demonstrate that character-based IRE is systematically implemented through the integration of religious values, discipline, responsibility, and social awareness within learning activities and madrasah culture. Teachers function as moral exemplars, while religious habituation programs serve as a hidden curriculum that strengthens the internalization of character values. This implementation signifies a paradigm shift in Islamic Religious Education from a predominantly cognitive orientation toward holistic character development encompassing cognitive, affective, and behavioral dimensions. The study provides empirical evidence that character-based IRE is a viable pedagogical approach to addressing contemporary moral and social challenges in Islamic secondary education.